Cortisol detection using a Long Period Fiber Grating Immunosensor coated with Graphene Oxide - Simone Soares; Ambra Giannetti; Flavio Esposito; Lucia Sansone; Anubhav Srivastava; Stefania Campopiano; Michele Giordano; Margarida Facão; Nuno F. Santos; Agostino Iadicicco; Carlos Marques; Francesco Chiavaioli (Sensors and Actuators Reports, 2025)
Recirculating Aquaculture Systems (RAS) have revolutionized the protein production sector in aquaculture, leading to significant growth and expansion of the industry. Despite the success of RAS in aquaculture, there are challenges related to stress in fish raised in these systems, which can impact their food intake, growth, and overall well-being. One of the major limitations in the aquaculture industry is the lack of smart sensors for real-time detection of stress hormones like cortisol, hindering our ability to understand and effectively manage the welfare of fish in these systems. In this work, a graphene oxide (GO) coated long period grating (LPG) was fabricated into a double-clad optical fiber (DCF) with W-shaped refractive index profile. The working point of the device was tuned to the mode transition region to enhance its sensitivity against outer medium changes. It was further integrated into a microfluidic system and the fiber surface was functionalized with specific anti-cortisol antibodies for the detection of cortisol. Finally, the performance of this immunosensor was evaluated for a cortisol concentration range of 0.01 ng/mL to 100 ng/mL, a wide working range of concentrations of relevant interest, achieving a limit of detection (LOD) of 0.06 ng/mL. Moreover, a selectivity test using testosterone and glucose as interfering substances was carried out.